2019
DOI: 10.3390/cancers11121944
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Hepatoblastoma and Recent Advances

Abstract: Hepatoblastoma is the most common childhood liver malignancy. The management of hepatoblastoma requires multidisciplinary efforts. The five-year overall survival is approximately 80% in developed countries. Surgery remains the mainstay of treatment for hepatoblastoma, and meticulous techniques must be employed to ensure safe and effective local control surgeries. Additionally, there have been several advances from both pediatric and adult literature in the way liver tumor surgery is performed. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 91 publications
0
44
0
Order By: Relevance
“…The probability of hepatoblastoma occurring in an infant or young child varies between 0.5 and 2 cases per million children per year. The explanation for this vast difference could be due to differing age groups and the possibility that the low hepatoblastoma values given in recent individual publications originate from "old" statistics, and therefore no longer accurately depict current incidence rates (29,30). Regional peculiarities supposedly play a subordinate role (25).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of hepatoblastoma occurring in an infant or young child varies between 0.5 and 2 cases per million children per year. The explanation for this vast difference could be due to differing age groups and the possibility that the low hepatoblastoma values given in recent individual publications originate from "old" statistics, and therefore no longer accurately depict current incidence rates (29,30). Regional peculiarities supposedly play a subordinate role (25).…”
Section: Epidemiologymentioning
confidence: 99%
“…The current therapeutic approach involves three treatment options: (i) pre-and/ or post-operative chemotherapy, (ii) tumorectomy with possible partial liver resection, and (iii) liver transplantation (29). The use of chemotherapies, including platinum compounds for neoadjuvant and adjuvant treatment of hepatoblastomas resulted in a significant improvement in outcome.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…[ 18 ] Due to the impressive liver regenerative capabilities in children, 75% to 85% of the liver parenchyma can be safely resected. [ 26 , 27 ] Ribero and colleagues suggested that TLV measured by CT was highly variable compared with TLV estimated on the correlation existing with the body surface area. [ 28 ] However, there is no widely - accepted estimation formula for children, thus we suggest use future liver remnant/body weight (FLR/BW) as an alternative instrument according to a minimal graft-recipient weight ratio (GRWR) of 0.8% employed in liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…If resection was deemed possible after NACT, children should undergo surgery with minimal delay. Children with HB who remain unresectable after NACT can be candidates for liver transplantation (LT) (37)(38)(39)(40). However, the cost and benefits of performing LT within an epidemic region should be carefully assessed.…”
Section: Patients With Hb Without Covid-19mentioning
confidence: 99%